Effect of entacapone, a peripherally acting catechol-O-methyltransferase inhibitor, on the motor response to acute treatment with levodopa in patients with Parkinson's disease. Issue 2 (February 1994) - Merello, M; Lees, A J; Webster, R; Bovingdon, M; Gordin, A
Abstract : Catechol-O-methyltransferase (COMT) inhibitors may be useful in the treatment of Parkinson's disease by improving the bioavailability of levodopa and by prolonging its effects. Entacapone (OR-611), a novel COMT inhibitor, which does not cross the blood brain barrier, was assessed in 12 patients with Parkinson's disease and motor fluctuations in a randomised, double-blind, cross-over, single dose study. The magnitude and duration of the therapeutic response to a single dose of 200 mg levodopa/50 mg carbidopa was evaluated after concomitant placebo, or 200 or 800 mg entacapone. A significant increase in the duration of the motor response to levodopa was seen when 200 mg entacapone was given with levodopa/carbidopa. Plasma levodopa concentrations were increased with both doses of the COMT inhibitor. The latency to onset of motor response did not differ significantly between active drug and placebo. Entacapone may prove useful in prolonging the duration of the benefit obtained from individual doses of levodopa.